2011
DOI: 10.1073/pnas.1019406108
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the synergistic antibiotic pair, lankamycin and lankacidin, in complex with the large ribosomal subunit

Abstract: The structures of the large ribosomal subunit of Deinococcus radiodurans (D50S) in complex with the antibiotic lankamycin (3.2 Å) and a double antibiotic complex of lankamycin and lankacidin C (3.45 Å) have been determined, in continuation of previous crystallographic studies on lankacidin-D50S complex. These two drugs have been previously reported to inhibit ribosomal function with mild synergistic effect. Lankamycin, a member of the macrolide family, binds in a similar manner to erythromycin. However, when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 27 publications
(24 reference statements)
1
41
0
Order By: Relevance
“…The SA50Stel structure shows that telithromycin is bound at the MLS B K-binding site and forms the typical ketolide (and macrolide) hydrogen bond between its desosamine sugar and A2058. At this position, it is partially blocking the protein exit tunnel, as has been found in other ribosome-MLS B K complex structures (5,27,50). In the SA50Stel complex, the flexible nucleotide A2062 is rotated compared with its conformation in native SA50S, and its conformational range is minimized by the hydrogen bond with A2503 (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…The SA50Stel structure shows that telithromycin is bound at the MLS B K-binding site and forms the typical ketolide (and macrolide) hydrogen bond between its desosamine sugar and A2058. At this position, it is partially blocking the protein exit tunnel, as has been found in other ribosome-MLS B K complex structures (5,27,50). In the SA50Stel complex, the flexible nucleotide A2062 is rotated compared with its conformation in native SA50S, and its conformational range is minimized by the hydrogen bond with A2503 (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Both induce Katushka2S expression, but the levels of induction are different. The binding sites of these two antibiotics are different: griseoviridin blocks A and P sites, while etamycin A binds adjacent to the peptidyl transferase center (PTC) at the peptide tunnel exit close to the macrolide's binding site (32). Effective induction of Katushka2S reporter by etamycin A is expected, due to the similarity with macrolides in both binding site and mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces rochei 7434AN4 produces two structurally unrelated polyketide antibiotics, lankacidin C ( 1 ) and lankamycin ( 2 ; Scheme ), and carries three linear plasmids pSLA2‐L, ‐M, and ‐S . The two antibiotics attract great attention because they inhibit peptide synthesis synergistically by binding to neighboring sites on the large ribosomal subunit . Nucleotide sequencing of the largest plasmid (pSLA2‐L, 210 614 bp) together with extensive mutational analysis revealed that the biosynthetic gene clusters for lankacidin ( lkc ) and lankamycin ( lkm ) are located on pSLA2‐L .…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Streptomycesr ochei 7434AN4 produces two structurally unrelated polyketide antibiotics, lankacidin C( 1)a nd lankamycin (2;S cheme 1), and carries three linear plasmids pSLA2-L, -M, and -S. [6] The two antibiotics attractg reat attention because they inhibit peptides ynthesis synergistically by bindingt o neighboring sites on the large ribosomal subunit. [7,8] Nucleotide sequencing of the largestp lasmid( pSLA2-L, 210 614 bp) together with extensive mutational analysisr evealed that the biosynthetic gene clusters for lankacidin( lkc)a nd lankamycin (lkm)a re located on pSLA2-L. [9] This plasmid contains two additional biosynthetic clusters, for ac ryptic type-II polyketide (roc) and ac arotenoid (crt). It also carriesm any regulatory genes, including ab iosynthetic gene srrX for the signaling molecules SRBs (S. rochei butenolides) and three tetR-type receptor genes (srrA, srrB,a nd srrC).…”
Section: Introductionmentioning
confidence: 99%